Disruptive technologies for promoting financial inclusion in South Africa - Aziz, Mahomed Asif (University of the Witwatersrand, Johannesburg, 2024)
This research study seeks to examine the dynamics of financial inclusion in South Africa via the prism of disruptive technologies, to detect stakeholder stances and suggest strategies for inclusive growth. Following an interpretive philosophy, the study used an inductive technique, conducting semi-structured interviews with 14 stakeholders from diverse industries. Thematic analysis was used to investigate the qualitative data, which yielded substantial results. The study's key results shed light on critical challenges. Stakeholders underlined the significance of inclusive policies targeted to different socioeconomic groups, as well as regulatory frameworks that encourage innovation while addressing economic concerns. Discussions focused on how economic factors like high interest rates and taxation affect entrepreneurship and technological innovation. Sustainable development became a key issue, emphasising the link between technical breakthroughs and global sustainability objectives. Furthermore, the study emphasises the government's responsibility to promote innovation and modernisation, pushing for strategic planning and more efficient bureaucratic processes. The implementation of Shariah law principles was noted as a noteworthy discovery, providing an opportunity to improve financial participation while lowering the dangers of indebtedness. Furthermore, the study emphasises the importance of talent transfer and cooperation as long-term growth drivers, as well as the benefits of information exchange and capacity building. These discoveries have far-reaching and complex ramifications. The study gives vital insights into consumer preferences, allowing banks to adjust their services to meet a wide range of demands. Policymakers might use the data to rethink existing restrictions and create initiatives that encourage innovation and financial inclusion. Socially, companies and schools may use the findings to promote economic empowerment and digital literacy. Overall, the research makes specific suggestions to South African stakeholders on how to create fair growth, boost innovation, and move forward with socioeconomic development goals
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Technologies; Financial inclusion; Disruptive technologies; South Africa; UCTD; SDG-8: Decent work and economic growth